Trajectories of parental involvement in home learning activities across the early years: associations with socio-demographic characteristics and children's learning outcomes. Issue 10 (3rd October 2018) - Hayes, Nicole; Berthelsen, Donna C; Nicholson, Jan M; Walker, Sue
ABSTRACT: This study examined the socio-demographic factors associated with trajectories of parental involvement in shared book reading and other home activities for children aged 2–6 years. The study uses data from 3836 families participating in Growing up in Australia: The Longitudinal Study of Australian Children . Latent growth curve models were estimated to describe associations between trajectories of parental involvement, socio-demographic factors, and children's learning outcomes. Higher levels of parental involvement at 2 years were associated with better learning outcomes at 6 years. On average, the frequency of parental involvement in home learning activities decreased over time. Family socio-economic disadvantage and being a male child were associated with lower levels of parental involvement at age 2 years, and more rapid decreases in parental involvement in home activities over time. Continued attention is needed to identify effective strategies that can address inequalities in children's home learning opportunities before children begin school.